2021
DOI: 10.1200/op.21.00307
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Remote Patient Monitoring (RPM) Program With Reduced Hospitalizations in Cancer Patients With COVID-19

Abstract: PURPOSE: The goal of this study was to assess the impact of an interdisciplinary remote patient monitoring (RPM) program on clinical outcomes and acute care utilization in cancer patients with COVID-19. METHODS: This is a cross-sectional analysis following a prospective observational study performed at Mayo Clinic Cancer Center. Adult patients receiving cancer-directed therapy or in recent remission on active surveillance with polymerase chain reaction–confirmed SARS-CoV-2 infection between March 18 and July 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…Remote monitoring has a clear impact on unscheduled hospitalizations, as there were no differences between the YP and OP groups. Pritchett et al also reported the positive impact of remote monitoring on unscheduled hospitalizations 16 . In fact, the use of remote monitoring was associated with a 78% relative risk reduction in hospital admission in their study 16 …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Remote monitoring has a clear impact on unscheduled hospitalizations, as there were no differences between the YP and OP groups. Pritchett et al also reported the positive impact of remote monitoring on unscheduled hospitalizations 16 . In fact, the use of remote monitoring was associated with a 78% relative risk reduction in hospital admission in their study 16 …”
Section: Discussionmentioning
confidence: 81%
“…Pritchett et al also reported the positive impact of remote monitoring on unscheduled hospitalizations. 16 In fact, the use of remote monitoring was associated with a 78% relative risk reduction in hospital admission in their study. 16 To our knowledge, this is the first study that assesses the use of PRO-based tolerance as a predictive factor of treatment response in OPs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a retrospective analysis of patients who engaged in the COVID-19 RPM program, we observed a significantly lower rate of 30-day, all-cause hospitalization (13.7% vs. 18.0%, P = 0.01), prolonged hospitalization >7 days (3.5% vs. 6.7%, P = 0.001), ICU admission (2.3% vs. 4.2%, P = 0.01), and mortality (0.5% vs. 1.7%, P = 0.01) when compared with those patients who were enrolled to the program but did not engage with the RPM technology ( 56 ). Further retrospective evaluation found that cancer patients with COVID-19 managed with RPM had a significantly lower hospital admission rate (2.8% vs. 13%, P = 0.002) compared with those managed without the program ( 68 ). Similar results were observed in a prospective, randomized, controlled trial of patients with chronic conditions who were monitored with or without RPM upon hospital discharge.…”
Section: Resultsmentioning
confidence: 96%
“…Outcomes associated with RPM reported in the literature have been mixed, with most strategies having been shown to positively impact patient management ( 44 ). Prior evaluations at Mayo Clinic have found that the use of RPM for supportive care for patients’ acute and chronic conditions has been associated with positive trends in acute care utilization, clinical outcomes, and total cost of care ( 56 , 67 , 68 ). In a retrospective analysis of patients who engaged in the COVID-19 RPM program, we observed a significantly lower rate of 30-day, all-cause hospitalization (13.7% vs. 18.0%, P = 0.01), prolonged hospitalization >7 days (3.5% vs. 6.7%, P = 0.001), ICU admission (2.3% vs. 4.2%, P = 0.01), and mortality (0.5% vs. 1.7%, P = 0.01) when compared with those patients who were enrolled to the program but did not engage with the RPM technology ( 56 ).…”
Section: Resultsmentioning
confidence: 99%